Investigation of the Efficacy of Asprosin Given with Brain Infusion Kit on Reproductive Organs and Testosterone Hormone in Male Rats - Kacar, Emine; Tan, Fatih; Ozdede, Mehmet Ridvan; Oz, Zeynep Dila; Serhatlioglu, Ihsan; Yilmaz, Bayram; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Intracerebroventricular; Testosterone; Organ weights; Rat